A Raman cell based on hollow core photonic crystal fiber for human breath analysis. Issue 9 (13th August 2014) - Chow, Kam Kong; Short, Michael; Lam, Stephen; McWilliams, Annette; Zeng, Haishan
Abstract : Purpose: : Breath analysis has a potential prospect to benefit the medical field based on its perceived advantages to become a point‐of‐care, easy to use, and cost‐effective technology. Early studies done by mass spectrometry show that volatile organic compounds from human breath can represent certain disease states of our bodies, such as lung cancer, and revealed the potential of breath analysis. But mass spectrometry is costly and has slow‐turnaround time. The authors' goal is to develop a more portable and cost effective device based on Raman spectroscopy and hollow core‐photonic crystal fiber (HC‐PCF) for breath analysis. Methods: : Raman scattering is a photon‐molecular interaction based on the kinetic modes of an analyte which offers unique fingerprint type signals that allow molecular identification. HC‐PCF is a novel light guide which allows light to be confined in a hollow core and it can be filled with a gaseous sample. Raman signals generated by the gaseous sample (i.e., human breath) can be guided and collected effectively for spectral analysis. Results: : A Raman‐cell based on HC‐PCF in the near infrared wavelength range was developed and tested in a single pass forward‐scattering mode for different gaseous samples. Raman spectra were obtained successfully from reference gases (hydrogen, oxygen, carbon dioxide gases), ambient air, and a human breath sample. The calculated minimum detectable concentration of this system was ∼15 parts per million by volume, determined by measuring the carbon dioxide concentration in ambient air via the characteristic Raman peaks at 1286 and 1388 cm −1 . Conclusions: : The results of this study were compared to a previous study using HC‐PCF to trap industrial gases and backward‐scatter 514.5 nm light from them. The authors found that the method presented in this paper has an advantage to enhance the signal‐to‐noise ratio (SNR). This SNR advantage, coupled with the better transmission of HC‐PCF in the near‐IR than in the visible wavelengths led to an estimated seven times improvement in the detection sensitivity. The authors' prototype device also demonstrated a 100‐fold improvement over a recently reported detection limit of a reflective capillary fiber‐based Raman cell for breath analysis. Continued development is underway to increase the detection sensitivity further to reach practical clinical applications.